PENGEMBANGAN MEDIA PEMBELAJARAN MONOPOLITAR PADA PEMBELAJARAN PPKN KELAS V DI SDN 2 PARANGTRITIS - Pratomo, Wachid; Nadziroh, Nadziroh; Chairiyah, Chairiyah; Noventamala, Ceriza Etsa (JURNAL PEKAN : Jurnal Pendidikan Kewarganegaraan, 2023)
The aims of this study were (1) to describe the product development in the form of monopoly learning media for Civics learning class V at SDN 2 Parangtritis, and (2) to describe the feasibility response of monopoly learning media for PPKn class V at SDN 2 Parangtritis. The method used is the research and development method (Research & Development or RnD) which consists of 5 stages, namely: analysis, design, development, implementation, and evaluation. For this research sample, the researcher took 6 class V students. Data collection techniques using observation, semi-structured interviews, questionnaires and documentation. The validation of monopoly learning media is given to two validators, namely material experts and media experts to determine the validity of the product being developed. Student response questionnaires were given to students to determine the quality of monopolistic learning media. Data were analyzed using quantitative analysis techniques. The results of this study are monopoly learning media in fifth grade PPKn learning on the application of the Pancasila precepts in everyday life. Monopolistic learning media obtains a feasibility percentage of 96% with very feasible criteria, while media experts obtain a feasibility percentage of 93% with very feasible criteria. Student responses from limited trials obtained a percentage of 94% with very decent criteria. So it can be concluded that monopoly learning media in class V Civics learning is very suitable to be used as a learning medium.Keywords: Learning Media, Monopoly, PPKn